Demographic Characteristics and Functional Performance of the Kidneys and Hearts of Patients with Acute Tramadol Toxicity - Mohammadpour, Abbas; Ashkezari, Mahmood Dehghani; Farahmand, Behrokh; Shokrzadeh, Mohammad (Drug Research, 2019)
Background Tramadol overdose is disproportionately more common in Iran, and in recent years, it has become one of the most common causes of poisoning admissions to emergency departments in this country. Tramadol is a synthetic analogue of codeine and a weak opioid receptor (μ) agonist that can cause seizures even in commonly used doses.Aims This study aimed to examine the relationship between seizure and plasma tramadol concentration in patients with tramadol poisoning who referred to one of the hospitals in Ghaemshahr, Iran.Study Design This research is an analytical cross-sectional study.Methods A total of 121 tramadol users (non-seizure group=61 and seizure group=60) were admitted to hospital. Demographic characteristics and clinical findings were collected by a questionnaire. Plasma was harvested after separation from blood cells and quantified using the HPLC method. Biochemical parameters, including urea, creatinine, troponin I, and creatine phosphokinase (CPK–MB) were determined by spectrophotometry. This study was a single blind design study.Results The mean age of participants was 25 years. Ninety-five participants were classified as smokers. The mean serum concentrations of tramadol in subjects with seizures and those without seizures were 491.90 μg/ml and 374.42 μg/ml (p=0.211), respectively. Average concentrations of biochemical parameters in the seizure group were 53.33 (9.38) µg/ml urea, 1.71 (0.29) µg/ml Cr, 6.53 (2.89) µg/ml TPI, and 58.23 (22.20) µg/ml CPK- MB. Average concentrations of biochemical parameters were significantly higher in the seizure group than in the non-seizure group (p<0.001).Conclusion Tramadol-induced seizures were not found to be related to age, gender, or dosage. This complication can lead to cardiac and renal complications in individuals on tramadol experiencing seizures. This result indicates that stricter restrictions should be imposed on the distribution and administration of the drug tramadol.
Keywords: Tramadol; Seizure; HPLC; Biochemical parameters